Implementation of Face-to-Face Learning after the Covid-19 Pandemic: Case Study at SD Muhammadiyah Pakel, Yogyakarta - Dewi Sarah Indah Harumi; Dholina Inang Pambudi (International Journal of Learning Reformation in Elementary Education, 2022)
After the Covid-19 pandemic, SD Muhammadiyah Pakel has carried out face-to-face learning (PTM) directly in the classroom and still adheres to health protocols. In PTM, it is necessary to prepare planning, implementation, and evaluation, as well as supporting and inhibiting factors. This study aimed to determine face-to-face learning planning, performance, and assessment at SD Muhammadiyah Pakel Yogyakarta. It is descriptive qualitative research as well as knowing the supporting and inhibiting factors of NCD. The subject consists of the principal, the teacher of 3rd grade and 4th grade. The results showed that the planning the implementation of face-to-face learning includes planning goals, materials, learning activities, learning tools, methods, learning resource media, and evaluations had been carried out. The implementation of face-to-face learning includes face-to-face learning factors that affect class management. Formative and summative assessments are supporting elements and inhibiting factors.